DEVELOPMENT OF RURAL DRINKING WATER DISTRIBUTION NETWORK IN BAYAT DISTRICT, KLATEN REGENCY - Wulandari, Misi
Drinking water supply system master plan for Klaten Regency 2015 – 2034 plans to develop access to drinking water in rural areas in Bayat District by increasing the piping network. The pipeline network in Bayat District has only reached 51.35%, so to achieve 100% of the pipeline network, a drinking water distribution network is developed. Network development is carried out with the stages of problem identification, goal setting, data collection, literature study, water demand projection, making 3 alternative networks, selecting the best alternative, and making technical drawings. There are 10 planned villages in Bayat District with 9 villages to be developed for distribution networks and 1 village is planned to design a new distribution network. At the end of the planning period, namely in 2034, the projected water demand for serving Bayat District is 97.48 lps. The drinking water distribution network to serve Bayat District is made of 3 alternatives for each planned village with a variety of routes that can be passed. Of the 3 alternatives, the best alternative was selected using the SAW method based on the criteria for investment costs, pressure, pipe velocity, and ease of construction. The results of the assessment show that the chosen alternative for the villages of Bogem, Jarum, Jambakan, Tegalrejo, and Jotangan is alternative 1; for Banyuripan, Gununggajah and Talang Villages, is alternative 2; and for Krakitan and Ngerangan Villages, is alternative 3. The distribution network is made by gravity flow and combination pattern with a total length of 53,695 km of the planned pipeline.